Comunicación y relaciones públicas para CQC Corp., con el fin de impulsar la formación artística integral en adolescentes del Distrito Metropolitano de Quito. Caso: Unidad Educativa San Francisco de Sales y Jim Irwin - Guamán Guilcapi, Lizeth Estefanía (2016)
The following work have been done with the objective of improving the perception and participation of teenagers in activities of artistic background, with the aim of informing it’s importance, and to motivate teenagers to be part of a society that participates on artistic activities. The development of the thesis is based on investigated theories and studies such as: Communication, Public Relationship and Artistic Formation. The investigation can determinate some aspects like the limit practice, not knowledge and low conscience about the importance of artistic formation in teenagers, letting the possibility to improve these terms. Wherefore, CQC Corp., considering the previous data, has the necessity of implementing the following communication and public relationship plan, in order to promote activities of artistic formation, achieving recognition and increasing the interest of teenagers about these activities. Next it will be detailed the theoretical part followed by a chapter based on research methodology, where arises objectives, methods and research instruments, which will be applied in the object of study. Finally, it will be presented the proposed Plan of Communication and Public Relations, with their respective strategies and actions to promote artistic education in teenagers of the Metropolitan District of Quito.